PEMBINAAN KWT MAKMUR JAYA MELALUI PELATIHAN PEMBUATAN BERBAGAI JENIS KOPIAH LAMPUNG UNTUK MEMOTVASI DALAM BERWIRAUSAHA - Irianti, Laksmi; Werena, Rosalia Dwi; Putra, Andius Dasa; Tiara, Tiara (FT Universitas Lampung, 2023)
The Women's Farmers Group serves as a platform for the community, particularly women,to manage and express various ideas in the field of agriculture as well as a way for group members tolearn and gain perspective. As a result, group activities are expected to be imaginative and up-to-date.The Makmur Jaya Women's Farmers Group has performed a number of functions that have benefitedthe community, including serving as a venue for learning through ordinary activities, training suppliedas a discourse of cooperation in welfare efforts for the community, and fostering creativity to increaseincome. Producing several types of traditional Lampung skullcaps as part of this activity would helpmembers of the Makmur Jaya women's farmer group to promote and enhance their creativity. Bycreating several styles of traditional Lampung skullcaps, this project intends to encourage and enhancethe creativity of the Makmur Jaya women's farmer group members. This would enable them to becomeentrepreneurs and boost the local economy by selling their handmade skullcaps as souvenirs. Trainingin the creation of skullcaps of various sorts and shapes will be conducted, with the assistance ofartisans from the Adian Tapis Lampung Foundation. Caps with Lampung-themed designs are thefinished product of this training and are ready for sale